Cryptococcal meningitis with secondary cutaneous involvement in an immunocompetent host - Tabassum, Saadia; Rahman, Atiya; Herekar, Fivzia; Masood, Sadia (The Journal of Infection in Developing Countries, 2013)
Cryptococcosis is a potentially fatal fungal disease caused by variants of Cryptococcus neoformans species. The respiratory tract is the usual portal of entry, with a peculiar predilection to invade the central nervous system. The skin can be secondarily involved in disseminated infection or be exceptionally involved as primary cutaneous infection by inoculation. The disease is mostly seen in immunodeficiency states. The diagnosis is frequently unsuspected in immunocompetent patients. We report a case of disseminated cryptococcal meningitis in an immunocompetent young adult. The cutaneous eruption prompted the accurate diagnosis. The patient, a 20-year-old female, had fever, cough, headache and intractable vomiting for the past two months and was being managed as a case of tuberculous meningitis. Two weeks after starting antituberculous treatment she developed umbilicated papules on the head and neck region. Necessary laboratory workup identified C. neoformans in cerebrospinal fluid (CSF) and skin specimens. The titers of cryptococcal antigen were measured in CSF and serum for diagnostic and prognostic purposes. Anti-fungal treatment resulted in regression of the cutaneous lesions and resolution of systemic complaints. The case highlights the need for high degree of suspicion, especially in healthy young adults, in the diagnosis of cryptococcosis. The cutaneous eruptions can be the first manifestation or a diagnostic clue of enormous significance.